The Efficacy and Safety of a Bacillus Probiotic Combination for the Treatment of Acute Diarrhea in Children: A Double-blind, Randomized, Placebo-controlled Multicentric Study - Ashish Ramchandra Dhongade; Sanjay Sudhakar Joshi; Suhas Venkatesh Kulkarni; Shashank S Jadhav; Neeta Nargundkar; Deepak Deshmukh; Anirudh Dilip Mehta (Pediatric Infectious Disease)
Objective: Probiotics have been researched extensively over the past few years for the prevention and treatment of diarrhea in pediatric populations. In the present study, the efficacy and safety of probiotic Bacillus subtilis HU58 and probiotic Bacillus coagulans SC208 in combination were evaluated in children for the treatment of acute diarrhea. Materials and Methods: In this randomized, double-blind, parallel, placebo-controlled trial, 64 children with average age of 4.18 ± 3.0 years (mean ± standard deviation), out of which 32 children with antibiotic-associated diarrhea (AAD) and 32 children with acute infective diarrhea randomly received either syrup containing B. subtilis HU58 and B. coagulans SC208 probiotics or placebo syrup daily for a period of 7 days. Stool consistency, duration of diarrhea in days, and abdominal pain intensity during the treatment period, were assessed daily in all subjects for the improvement in clinical signs and symptoms. Also, an assessment of adverse events was done from the screening visit to the end of study visit. Result: A total of 32 subjects were screened and randomized in both cohort 1 and cohort 2. At the end of the study, that is, on day 7, B. subtilis HU58 + B. coagulans SC208 syrup-treated subjects in both cohorts showed significant improvement in stool consistency and duration of diarrhea over placebo syrup. No adverse events were observed in the study of both cohorts. Conclusion: This study’s results conclude that B. subtilis HU58 and B. coagulans SC208 syrup improved the recovery and reduced the course of acute infectious diarrhea and AAD in children, with no reported adverse effects.